2011
DOI: 10.4103/1119-3077.84007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of aggression among psychiatric in-patients at Jos University Teaching Hospital

Abstract: Aggression is a significant clinical problem in psychiatric facilities. Consequences of aggression among psychiatric patients can be far reaching for the mental health worker. More longitudinal studies should be carried out among specific diagnostic categories of psychiatric patients to determine factors associated with aggression in each.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
3
18
1
Order By: Relevance
“…In contrast to previous studies, the current study found a significant difference between sex with regard to type and frequency of aggression (Flannery et al ., ; McKenzie & Curr, ; Grassi et al ., ). The results of this study are consistent with the findings of Chukwujekwu and Stanley (), who found that the aggressive incidents recorded in the ward were perpetrated more by men than by women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast to previous studies, the current study found a significant difference between sex with regard to type and frequency of aggression (Flannery et al ., ; McKenzie & Curr, ; Grassi et al ., ). The results of this study are consistent with the findings of Chukwujekwu and Stanley (), who found that the aggressive incidents recorded in the ward were perpetrated more by men than by women.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of aggressive behaviors among psychiatric inpatients in this study was 23.6%. This is consistent with studies conducted elsewhere, which suggest a range of 5–25% (Amoo & Fatoye, ; Krüger & Rosema, ; Chukwujekwu & Stanley, ). This study contributes to the literature by suggesting that there is a need for mental health professionals to have skills in managing aggressive behavior to prevent incidences of harm and to ensure the safety of service users and staff.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MOAS assessments were performed retrospectively in addition to using prospectively collected clinical and sociodemographic data as possible predictors of aggression and hostility. The overall incidence of aggression and hostility in patients diagnosed with schizophrenia was 31%, which is similar to that reported by many authors (e.g., Arango, Barba, Gonzalez-Salvador, & Ordonez, 1999;Chukwujekwu & Stanley, 2011;Craig, 1982;McNiel & Binder, 1986;Rossi et al, 1985;Tardiff, Marzuk, Leon, Portera, & Weiner, 1997;Tardiff & Sweillman, 1980). We did not find significant gender differences between aggressive and non-aggressive hospitalized patients diagnosed with schizophrenia.…”
Section: Discussionsupporting
confidence: 88%
“…These factors were more likely to be male, less than 45 years old, and those from diagnosis of schizophrenia (Chukwujekwu & Stanley, 2011;Pearson et al, 1986) use of temporary nursing staff (James, Fineberg, Shah, & Priest, 1990); previous aggressive and disturbed behavior (Noble & Rodger, 1989); criminal record and previous drug abuse (Walker & Seifert, 1994).…”
Section: Introductionmentioning
confidence: 99%